Analisis Faktor yang Mempengaruhi Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas II SDN Podorejo 02 Menggunakan Model Pembelajaran Problem Based Learning - Arini Widi Utami; Bunga Anggun Prabawati; Jasmine Diva Auranisa; Ananta Destian Murtiana; Arif Maulana; Trimurtini T (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Students' low problem-solving abilities are reflected in their difficulty answering non-routine questions, which prevents them from developing ideas and skills. By using the problem-based learning (PBL) model and students' initial mathematics ability (KAM), this research aims to determine the level of students' mathematical problem-solving abilities and find out what factors influence students' mathematical problem-solving abilities. The research method used is descriptive-qualitative. The findings of this research show how the problem-based learning approach increases students' capacity to solve mathematical problems. Based on the overall data analysis that has been carried out, it was found that the application of the problem-based learning model had a positive impact on developing problem-solving and understanding skills for class II SDN Podorejo 02. The results of the analysis showed that the majority of students succeeded in answering the questions without the help of the teacher, but there were still difficulties in certain aspects, such as understanding questions and problem-solving strategies.